A new ex vivo beating heart model to investigate the application of heart valve performance tools with a high-speed camera - Kondruweit, Markus; Friedl, Sven; Heim, Christian; Wittenberg, Thomas; Weyand, Michael; Harig, Frank (Asaio Journal, 2014)
High-speed camera examination of heart valves is an established technique to examine heart valve prosthesis. The aim of this study was to examine the possibility to transmit new tools for high-speed camera examination of heart valve behavior under near-physiological conditions in a porcine ex vivo beating heart model. After explantation of the piglet heart, main coronary arteries were cannulated and the heart was reperfused with the previously collected donor blood. When the heart started beating in sinus rhythm again, the motion of the aortic and mitral valve was recorded using a digital high-speed camera system (recording rate 2,000 frames/sec). The image sequences of the mitral valve were analyzed, and digital kymograms were calculated at different angles for the exact analysis of the different closure phases. The image sequence of the aortic valve was analyzed, and several snakes were performed to analyze the effective orifice area over the time. Both processing tools were successfully applied to examine heart valves in this ex vivo beating heart model. We were able to investigate the exact open and closure time of the mitral valve, as well as the projected effective orifice area of the aortic valve over the time. The high-speed camera investigation in an ex vivo beating heart model of heart valve behavior is feasible and also reasonable because of using processing feature such as kymography for exact analysis. These analytical techniques might help to optimize reconstructive surgery of the mitral valve and the development of heart valve prostheses in future.
EVALuna2:16086